Towards understanding the bee fauna of the family Halictidae (Hymenoptera: Apoidea) of Apsheron Peninsula - Kh.A. Aliev (Кавказский энтомологический бюллетень, 2005)
Bees of the family Halictidae of the fauna of Apsheron Peninsula, Azerbaijan, are represented by 52 species, among which 15 are new to the fauna of Azerbaijan: Dufourea halictula, Nomioides nigripes, N. turanicus, N. modestus, Halictus senilis, Evylaeus malachurus, E. longyrostre, Sphecodes croaticus, Vestitohalictus tectus, V. radoszkowskii, Seladonia cephalicus, Sphecodes geoffrellus, Sph. miniatus, Sph. marginatus, Sph. nasica. Brief biotopical and ecological data are given for all 52 species